2016
DOI: 10.5114/wiitm.2016.62135
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of male sexual function in bariatric patients.

Abstract: IntroductionObesity is associated with numerous comorbidities and affects various aspects of life, including sexual functioning. Bariatric surgery is an effective treatment for obese people. Male sexual function after bariatric surgery is not well known.AimTo compare male sexual function and sexual quality of life after surgical weight loss with controls seeking bariatric surgery.Material and methodsInternational Index of Erectile Function and Sexual Quality of Life-Male (SQoL-M) questionnaires were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…A study of women before and after bariatric surgery found that women before the procedure assessed the quality of sex life at 60.0 and women after the surgery −75.0 (Janik et al, 2015 ). Similar studies were conducted among men—in the control group, the quality of sexual life was 81.8 and in the group after the surgery −88.6 (Janik et al, 2016 ).…”
Section: Discussionsupporting
confidence: 53%
“…A study of women before and after bariatric surgery found that women before the procedure assessed the quality of sex life at 60.0 and women after the surgery −75.0 (Janik et al, 2015 ). Similar studies were conducted among men—in the control group, the quality of sexual life was 81.8 and in the group after the surgery −88.6 (Janik et al, 2016 ).…”
Section: Discussionsupporting
confidence: 53%
“…While discussing the demography of the participants, we were surprised by the almost even gender ratio, which was typically dominated by female participants in other studies and our previous observations regarding bariatric surgery [ 9 , 15 17 ].…”
Section: Discussionmentioning
confidence: 61%
“…The efficacy of bariatric surgery, considering improvement in the comorbidity course, daily functioning and quality of life has already been established. [20][21][22][23] Despite benefits of bariatric surgery, there are serious concerns about the perioperative safety of the elderly population, who may have a higher anesthesia-related perioperative risk, also influenced by a higher prevalence of comorbidities. [6] Preliminary data on bariatric surgery in elderly patients reveal controversial results.…”
Section: Discussionmentioning
confidence: 99%